Amphetamine use in the fourth decade of life: Social profiles from a population‐based Australian cohort. (11th July 2018) - Butterworth, Peter; Becker, Denise; Degenhardt, Louisa; Hall, Wayne D.; Patton, George C.
Abstract: Introduction and Aims: To estimate the prevalence and frequency of amphetamine use in a cohort of Australians aged in their mid‐30s. Design and Methods: Cross‐sectional analysis of wave 10 data collected in 2014 from the Victorian Adolescent Health Cohort Study: a sample of 1435 persons originally selected in a stratified, random community survey of secondary school students from the state of Victoria that commenced in 1992. Weighted multinomial regression models were used to evaluate the social, health and other substance‐use correlates of lifetime and current (12‐month) amphetamine use and current frequency of use. Results: Lifetime amphetamine use was reported by 23.2% (95% confidence interval 21.0–25.5%) of respondents, and 6.5% (95% confidence interval 5.2–7.8%) reported current (12‐month) use. A quarter (26%) of those currently using amphetamines, 1.7% (95% confidence interval 1.0–2.4%) of all respondents, reported frequent (at least weekly) use. Men reported greater amphetamine use than women. Current amphetamine use was associated with disrupted family circumstances, socioeconomic adversity, polydrug use and high levels of drug use within the social and familial environment. Frequent use was associated with greater likelihood of multiple adversity, unemployment, anxiety disorders and use of mental health services. Discussion and Conclusions: The current results show that lifetime, current and frequent amphetamine use was common amongst adults in the fourth decade of life in this cohort, and associated with the experience of social disadvantage, poor mental health and living in a social context in which drug use is the norm.